The complex stellar populations in the background of open clusters in the third Galactic quadrant - Carraro, Giovanni (2016)
Multi-color photometry of the stellar populations in five fields in the third Galactic quadrant centred on the clusters NGC 2215, NGC 2354, Haffner 22, Ruprecht 11, and ESO489 SC01 is interpreted in terms of a warped and flared Galactic disk, without resort to an external entity such as the popular Monoceros or Canis Major overdensities. Except for NGC 2215, the clusters are poorly or unstudied previously. The data generate basic parameters for eachcluster, including the distribution of stars along the line of sight.We use star counts and photometric analysis, without recourse to Galactic-model-based predictions or interpretations, and confirms earlier results for NGC 2215 and NGC 2354. ESO489 SC01 is not a real cluster, while Haffner 22 is an overlooked cluster aged 2.5 Gyr. Conclusions for Ruprecht 11 are preliminary, evidence for a cluster being marginal. Fields surrounding the clusters show signaturesof young and intermediate-age stellar populations. The young population background to NGC 2354 and Ruprecht 11 lies 8?9 kpc from the Sun and 1 kpc below the formal Galactic plane, tracing a portion of the Norma-Cygnus arm, challenging Galactic models that adopt a sharp cut-off of the disk 1214 kpc from the Galactic center. The old population is metal poor with an age of 2 3 Gyr, resembling star clusters like Tombaugh 2 or NGC 2158. It has a large color spread and is difficult to locate precisely. Young and old populations followa pattern that depends critically on the vertical location of the thin and/or thick disk, and whether or not a particular line of sight intersects one, both, or none.